Chomsky's Universal Grammar: A Case of Its Concepts of Government/Binding Theory - Harsono, Y M (TEFLIN Journal, 2015)
The purpose of this paper is to see the universality of the Government/Binding Theory in its concepts of government, the pro-drop parameter, and binding theory. Three languages English, Indonesian, and Javanese are analyzed based on the three concepts. From the analysis it is concluded that in some cases language is universal, but in some other cases every language is specific.